مستقبل الترجمة في الوطن العربي - عزالدين، سعودي حسن سالم (جامعة دنقلا - كلية الدراسات العليا, 2017)
هدفت الورقة إلى تسليط الضوء على واقع ومستقبل الترجمة في الوطن العربي" وقد تمثلت المشكلة في تدني هذا الواقع وضبابية الرؤية عند استشراف آفاق المستقبل. وقامت الورقة على افترض أن العمل المترجم يجب أن يقضي إلى تراكم معرفي يمكن بدوره أن بفضي إلى نهضة علمية وفكرية تنهي حقبة الركود. واستخدمت الورقة المنهج التاريخي والمنهج الوصفي التحليلي. وتوصلت الورقة إلى نتيجة رئيسة مفادها أن واقع الترحمة في الوطن العربي لا يبعث على التفاؤل بسبب ما يكتنفه من معوقات ومشكلات تجعل المستقبل امتدادا للحاضر المدحور. وقد خرجت الورقة بعدة توصيات، أهمها: ضرورة الاعتناء بالبنية التحتية للترجمة والنشر وتعليم اللغات في الوطن العري، والتكامل والتنسيق بين دوله ومنظماته العاملة في مجال الترجمة، ومأسسة عملية الترجمة.
The paper aimed to shed light on the reality and future of translation in the Arab World. The problem is embodied in the deterioration of this reality and the ambiguous vision when exploring future horizons. The paper was based upon the assumption that the translated work should lead to a knowledge accumulation that in turn will lead to a scientific and intellectual renaissance to curb the recession period. The paper used the historical descriptive analytic approach. The main result concluded by the paper was that the reality of the translation is not so optimistic due to the prevailing obstacles and problems that make the future an extension of the defeated past. Finally, the paper pointed out several recommendations, the most significant being; enhancement of the translation and publishing infrastructure and language teaching in the Arab World, integration and coordination between Arab countries and translation organizations and institutionalization of the translation process.
Keywords: الترجمة -- المترجم -- الوطن العربي